Glucocorticoid induced adrenal insufficiency in children: Morning cortisol values to avoid LDSST - Laulhé, Margaux; Dumaine, Cécile; Chevenne, Didier; Leye, Fallou; Faye, Albert; Dozières, Blandine; Strullu, Marion; Viala, Jérome; Hogan, Julien; Houdouin, Véronique; Léger, Juliane; Simon, Dominique; et al. (Frontiers in Pediatrics, 2022)
Objectives Glucocorticoid-induced adrenal insufficiency (GI-AI) is a common side effect of glucocorticoid therapy. However, its diagnosis currently relies on the realization of a Low Dose Short Synacthen Test (LD-SST) that requires an outpatient hospital and several blood samples. Our goal was to evaluate whether morning cortisol values could predict the response to LD-SST, in children, to avoid useless dynamic tests and facilitate diagnosis of glucocorticoid induced adrenal insufficiency. Study Design. We recorded data of 91 pediatric patients who underwent a LD-SST in our center between 2016 and 2020 in a retrospective observational study. We selected LD-SST realized following administration of supra-physiologic doses of glucocorticoids during more than 3 weeks and performed at least four weeks after treatment was stopped. Adrenal deficiency was defined as a plasma cortisol concentration inferior to 500 nmol/L at LD-SST. Results Glucocorticoid-induced adrenal insufficiency was diagnosed in 60% of our cohort. Morning cortisol values were predictive of the response to the LD-SST (AUC ROC 0.78). A plasma cortisol concentration of less than 144 nmol/L predicted glucocorticoid induced adrenal insufficiency with a specificity of 94% and a value over 317 nmol/L predicted recovery of the HPA axis with a sensitivity of 95%. We did not find any other predictive factor for glucocorticoid-induced adrenal insufficiency. Conclusions Morning cortisol values can safely assess recovery of the HPA axis in children treated chronically with glucocorticoids. Using these thresholds, more than 50% of LD-SST could be avoided in children.